O Auto do Santo Preto e a bênção das três fomes: a carnavalização-afeto das festividades jurunenses de São Benedito em Belém do Pará - CHAGAS, Eduardo Wagner Nunes (Universidade Federal do Pará, 2021)
This work reflects the immersion of the last ten years of my life in the steps of the many processions, parties, litanies, dawns that are part of the complex of events that make up the festivities dedicated to São Benedito, held annually in the Jurunas neighborhood, in Belém do Pará, between the end of July and the beginning of August. Immersion lived in the flesh of a carnival-ethno-devotee, through which I perceive these festivities as spectacular cultural practices, possessing an exquisite symbolic vocabulary having the function of a line that borders and unites memories, belonging, identities, identifications, singularities, in a single banner, circumventing social tensions; actions supported by what I call carnavalizationaffection, a concept formulated in the light of understandings of carnivalization, party and affections, from Mikhail Bakhtin, Émile Durkheim, Michel Maffesoli and Davi Le Breton. In its epistemological horizon, the work is built on the glimpse of the world as a text, through the vision of Paul Ricouer, of interpretive anthropology, of Clifford Geertz, of the comprehensive and orgiastic sociologies, of Michel Maffesoli, and of the anthropology of emotions, of Davi Le Breton. In its methodological perspective, added to its epistemological horizon, the work is an ethnocenological product, bringing the experience of the researcher as a tool of the gaze, from which emerges the concept of spectacularity and the glimpse of these parties as Spectacular Organized Human Practices and Behaviors. Finally, the work translates into the burlesque reading of the samba schools' carnival, guiding the research of Benedictine processions through the spectacular look of a samba school plot, bringing together, in the same embroidery, research, artistic life and affects that emanate from me and me.